Opto-electronic properties of blue phosphorene oxide with and without oxygen vacancies (2020)
Blue phosphorene is an attractive nanomaterial that exhibits some remarkable optoelectronic properties. Various studies have verified its ability to adsorb gaseous compounds and, in particular, to dissociate O2, forming covalent bonds between phosphorus and oxygen atoms. These covalent bonds could be the reason behind the oxidation reaction that affects the blue phosphorene in normal room conditions. Theoretically, it has been demonstrated that the blue phosphorene oxide (BPO) is just as stable as the blue phosphorene. Given that metallic oxides are widely used as catalyzers and gas sensors, this opens the possibility of the BPO being presented as a gas sensor as well. For all the above, in this work the optoelectronic properties of BPO were studied, along with the generation of the oxygen vacancies. The investigation was performed within the density functional theory (DFT). In the study of the oxygen vacancy, the formation energy was calculated, and the results are similar to the formation energies of oxygen vacancies in other known oxides. It was found that the BPO with a single vacancy has a favorable energetic stability. The characterization of the vacancy is achieved using the electronic structure and the optical response. Additionally, the analysis of the adsorption of a hydrogen atom on the BPO, and the subsequent formation of hydroxide is presented. © 2019 Wiley Periodicals, Inc.